2001
DOI: 10.1111/1467-7687.00147
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurences of preverbal vocal behavior and motor action in early infancy

Abstract: This study reports on co-occurrence of vocal behaviors and motor actions in infants in the prelinguistic stage. Four Japanese infants were studied longitudinally from the age of 6 months to 11 months. For all the infants, a 40 min sample was coded for each monthly period. The vocalizations produced by the infants co-occurred with their rhythmic actions with high frequency, particularly in the period preceding the onset of canonical babbling. Acoustical analysis was conducted on the vocalizations recorded befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 22 publications
2
86
1
2
Order By: Relevance
“…When systems of this type are coupled, they are typically termed 'coupled oscillators;' and it is a well-established characteristic of coupled oscillators that each tries to draw the other into its characteristic oscillation pattern. This suggests the possibility that entrainment, which occurs when the activation of one oscillator is sufficient to "pull in" the activity of the other to yield an ordered patterning of coordinated activity, may characterize the development of vocal-motor coordination (see Iverson & Fagan, 2004, for discussion and relevant data; see also Ejiri & Masataka, 2001). Iverson and Thelen (1999) characterize the emergence of reduplicated babble as a product of the entrainment of the vocal by the motor system.…”
Section: Group Patterns Of Delaymentioning
confidence: 99%
“…When systems of this type are coupled, they are typically termed 'coupled oscillators;' and it is a well-established characteristic of coupled oscillators that each tries to draw the other into its characteristic oscillation pattern. This suggests the possibility that entrainment, which occurs when the activation of one oscillator is sufficient to "pull in" the activity of the other to yield an ordered patterning of coordinated activity, may characterize the development of vocal-motor coordination (see Iverson & Fagan, 2004, for discussion and relevant data; see also Ejiri & Masataka, 2001). Iverson and Thelen (1999) characterize the emergence of reduplicated babble as a product of the entrainment of the vocal by the motor system.…”
Section: Group Patterns Of Delaymentioning
confidence: 99%
“…In a longitudinal study, Ejiri and Masataka (2001) examined cooccurrences between vocalization and motor activity in 4 infants observed monthly in naturalistic in-home play sessions between the ages of 6 and 11 months. They coded vocalizations and four types of motor activity (mouthing, manipulating, banging, and rhythmic actions) and noted all instances of co-occurrence between vocal and motor behaviors, defined as a temporal overlap between behaviors of more than 1 s. The authors reported that, in general, a higher percentage of vocalizations co-occurred with rhythmic movements than with other types of motor behaviors.…”
Section: Vocal-rhythmic Movement Coordination In Infancymentioning
confidence: 99%
“…She interpreted both activities as variants in bringing about vocal tract closure and constriction. In an additional study of 4 infants between 6 and 11 months, Ejiri and Masataka (2001) documented both the frequent occurrence of mouthing and co-occurrences of mouthing and vocalization; however, they did not describe the characteristics of co-occurring vocalizations. Descriptions of vocalizations that co-occur with mouthing may be important for three reasons: Mouthing is an exploratory behavior that may extend to encompass exploration of co-occurring vocalizations; the peak period of mouthing behavior in infancy coincides with and may contribute to advances in consonant production; and mouthing, which appears to contribute to the development of multimodal object perception, may also contribute to the development of multimodal speech perception.…”
Section: Introductionmentioning
confidence: 95%